Discrete time variable structure control method for seismic excited building structures with time delay in control. - Cai, Guoping
The discrete time variable structure control method for seismically excited linear structures with time delay in control is investigated in this paper. The control system with time delay is first discretized and transformed into standard discrete form which contains no time delay in terms of the time delay being integer and non-integer times of sampling period, respectively. Then the discrete switching surface is determined using ideal quasi sliding mode and discrete controller is designed using the discrete approach law reaching condition. The deduced controller and switching surface contain not only the current step of state feedback but also linear combination of some former steps of controls. Numerical simulations are illustrated to verify the feasibility and robustness of the proposed control method. Since time delay effect is incorporated in the mathematical model for the structural control system throughout the derivation of the proposed algorithm, system performance and dynamic stability are guaranteed.
Keywords: Time delay; Discrete time variable control; Linear structure; Discrete switching surface; Quasi-sliding mode; Approach law reaching condition